The effect of Ni or Co additions on the structure of Zr60Cu30Al10 bulk metallic glass revealed by high-energy synchrotron radiation - Stiehler, Martin E.; Panagiotopoulos, Nikolaos T.; Keeble, Dean S.; Ivanov, Yurii P.; Menelaou, Melita; Jolly, Mark R.; Greer, A. Lindsay; Georgarakis, Konstantinos (Elsevier, 2022)
The effect of substituting Cu by elemental additions of Ni or Co on the atomic structure of the Zr60Cu30Al10 ternary bulk metallic glass (BMG) is studied using high-energy synchrotron radiation X-ray diffraction. Analyses of the structural features in reciprocal and real space using the structure factors S(Q) and pair-distribution functions (PDF) point to an increase in the structural disorder for the Ni- or Co-bearing quaternary alloys. This is consistent with the “confusion principle” since upon alloying the initially nearly identical atomic sizes of Cu, Ni and Co diversify due to local electronic interactions. In real space, the disordering is manifested by a reduced deviation from the average particle density visible in the nearest-neighbour (NN) atomic shell structure over the complete short- and medium-range order region. Despite their similar atomic size, enthalpies of mixing with the main alloy elements and apparent disordering of the structure, the additions of Ni or Co have different effects on thermal stability of the ternary “mother” alloy.
Keywords: Metallic glass; Atomic structure; Pair distribution function; Glass forming ability; X-ray diffraction; Synchrotron radiation; Disorder; Confusion principle; Anti-shell; Emergence; TEM; DSC